2014
DOI: 10.4236/psych.2014.510141
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Work-Stress, Psychological Stress and Staff Health and Work Outcomes in Office Workers

Abstract: This study examined associations between work-stress, perceived organizational support, supervisor support, staff health (i.e., psychological stress, anxiety, depression, fatigue), and work outcomes (i.e., turnover intentions, organizational commitment, job satisfaction). A heterogeneous sample of 201 office staff recruited via email and snowball sampling completed a short anonymous online survey asking about their recent experiences of the above factors. High work-stress was associated with worse staff health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 40 publications
2
29
0
2
Order By: Relevance
“…This study addressed the role of social support as a moderator or as a main effect on the relationship between self-reports of work stressors and stress-related symptoms, controlling for negative affectivity. Regarding NA, the results support the recommendation of that job stress research should include NA as a relevant factor [10] [12] [14] [16] [17]. Researchers have argued that the stressor-stress symptom relationship may be overstated and even spurious if NA is not included in the analysis.…”
Section: Discussionsupporting
confidence: 63%
“…This study addressed the role of social support as a moderator or as a main effect on the relationship between self-reports of work stressors and stress-related symptoms, controlling for negative affectivity. Regarding NA, the results support the recommendation of that job stress research should include NA as a relevant factor [10] [12] [14] [16] [17]. Researchers have argued that the stressor-stress symptom relationship may be overstated and even spurious if NA is not included in the analysis.…”
Section: Discussionsupporting
confidence: 63%
“…Perhaps emotional stability influenced the relationships between job stress and other outcomes. Job stress might result in a significant relationship with, for instance, employee turnover intention (Bridger et al, 2013;Thorsteinsson et al, 2014) and job dissatisfaction (Cheng et al, 2014).…”
Section: Possible Limitations and Future Directionsmentioning
confidence: 99%
“…Despite there being no current studies in sport which examine the relationships between organisational stressors (as measured on the OSI-SP) and the above outcomes, there is research in alternative occupations which can be used to support and underpin this exploratory hypothesis. Cooper, Dewe, and O'Driscoll (2001), for example, discuss a body of literature which has found that occupational stressors (e.g., organisational roles, work relationships, career development) can be associated with various job related strains and individuals' psychosocial well-being and performance (see also Navya, & Sandhya, 2014;Sullivan & Bhagat, 1992;Thorsteinsson, Brown, & Richards, 2014).…”
mentioning
confidence: 99%